2017
DOI: 10.1016/j.juro.2017.01.103
|View full text |Cite
|
Sign up to set email alerts
|

An Update of the American Urological Association White Paper on the Prevention and Treatment of the More Common Complications Related to Prostate Biopsy

Abstract: This white paper provides a concise reference document for the more common prostate biopsy complications and prevention strategies. Risk assessment should be performed for all patients to identify known risk factors for harboring fluoroquinolone resistance. If infection incidence increases check the local antibiogram, current equipment and cleaning practices, and consider alternate approaches to antibiotic prevention such as needle cleaning, risk basked augmentation, rectal culture with targeted prophylaxis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
167
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 20 publications
6
167
1
5
Order By: Relevance
“…Transrectal ultrasonography (TRUS)-guided prostate biopsy is an invasive urological procedure that is commonly performed in the clinical setting and puts patients at increased risk of UTI and urosepsis. The rate of sepsis after TRUS-guided prostate biopsy ranges from 0.3 to 3.5% 24,25 and a 2016 population-based study found that infectious complications after biopsy are increasing 26 . This increase might be in part caused by an increase in bacterial resistance to fluoroquinolones, which are commonly given as prophylaxis, thereby prompting some clinicians to shift to using broader-spectrum antibiotics such as gentamicin and ceftriaxone, or combinations of antibiotics 24,27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transrectal ultrasonography (TRUS)-guided prostate biopsy is an invasive urological procedure that is commonly performed in the clinical setting and puts patients at increased risk of UTI and urosepsis. The rate of sepsis after TRUS-guided prostate biopsy ranges from 0.3 to 3.5% 24,25 and a 2016 population-based study found that infectious complications after biopsy are increasing 26 . This increase might be in part caused by an increase in bacterial resistance to fluoroquinolones, which are commonly given as prophylaxis, thereby prompting some clinicians to shift to using broader-spectrum antibiotics such as gentamicin and ceftriaxone, or combinations of antibiotics 24,27 .…”
mentioning
confidence: 99%
“…The rate of sepsis after TRUS-guided prostate biopsy ranges from 0.3 to 3.5% 24,25 and a 2016 population-based study found that infectious complications after biopsy are increasing 26 . This increase might be in part caused by an increase in bacterial resistance to fluoroquinolones, which are commonly given as prophylaxis, thereby prompting some clinicians to shift to using broader-spectrum antibiotics such as gentamicin and ceftriaxone, or combinations of antibiotics 24,27 . However, shifting to more potent antibiotics is inconsistent with the goal of improving antimicrobial stewardship and could further increase resistance.…”
mentioning
confidence: 99%
“…This is corroborated by studies showing that bacteria in rectal flora are typically sensitive to FMT and the worldwide increase in bacterial resistance to fluoroquinolones [23][24][25]. Moreover, Liss et al [26] reported that the main cause of UTI following transrectal procedures is the presence of FQR bacteria, usually E. coli. Thus, given the high prevalence of CIP resistance and the lower efficacy of CIP in preventing TRUS-PNB-related UTIs, a safer alternative to CIP for TRUS-PNB prophylaxis should be strongly considered.…”
Section: Discussionmentioning
confidence: 79%
“…However, the main concern regarding the use of fluoroquinolones as prophylactic antibiotics is its high incidence of bacterial resistance [63]. Therefore, a rectal swab culture and subsequent targeted antibiotic prophylaxis are used to decrease the incidence of bacterial resistance [64]. A meta-analysis by Roberts et al has shown targeted prophylaxis to significantly reduce infection rates when compared to empirical prophylaxis [65].…”
Section: Transrectal or Transperineal Approachmentioning
confidence: 99%